Análise de modelos de distribuição transversal de cargas em superestruturas de viga em seção caixão de pontes e viadutos alargados - Fontana, Patricia (2015)
The present work shows a comparison between results of the structural analysis of a cellular box cross section viaduct superstructure, the results are obtained with analytic simplified methods and with the finite element method using a suitable software, aiming the validation of the methods used for constructions in cellular box cross section, observing the criteria of time, cost and satisfactory results. The stress transversal distribution coefficients for the superstructure of a box cross section viaduct were analyzed for the expansion of the construction with the use of box cross section with different dimensions from the original one and with no symmetry, regarding the expansion only for one side of the construction. Such determination presents a huge importance, once the knowledge of the transversal distributions among the stringer beams that comprise the construction allows the elaboration of more accurate bridge widening designs, searching for the best approximation between the numerical models and the real behavior of the structure. The results showed that the three-dimensional models are those that are closer to the real condition of the structure, but with high level of complexity for development and a high demand of time. The grid model and the model based on the Fauchart’s theory show different results of the three-dimensional models, proving to be conservative and with inaccurate answers, not being indicated for the analysis of box cross section structures. On the other hand, the Mason’s Method showed good results, with values close to the ones of the three-dimensional models, however with a shorter time of development and delivery of results, featuring an efficient method for box cross section artworks widening studies, when analyzing the criteria of cost, time and results.